ANALISIS KONDISI FISIK KIPER FUTSAL SMA SE – KOTA MATARAM TAHUN 2020 - Gora Wahyu Darma Saputra; Andi Anshari Bausad; Sri Erny Mulyani (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2020)
The background in this study is the physical condition of high school futsal goalkeepers in the city of Mataram. The purpose of this study was to determine the physical condition of high school futsal goalkeepers in Mataram in 2020. The research method used by researchers is the method of action tests and documentation. The sample selection used non-random sampling method with purposive sampling technique. Analysis of the data used in this study using quantitative descriptive analysis techniques with percentages. The results of a series of tests showed that 33.33% less bleep test, 33.33% less whole body reaction, 58.33% less shuttle run, and 16.66% less category flexibility. So the conclusion is "the physical condition of high school futsal goalkeepers in Mataram in 2020 is categorized as poor